2000
DOI: 10.1890/0012-9615(2000)070[0021:daieop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Predation by Common Eiders and Abiotic Disturbance in an Intertidal Community

Abstract: Predation and disturbance have been well studied in intertidal communities. However, the impact of vertebrate predators, particularly waterfowl, has been only infrequently determined in long‐term intertidal studies. Using predator exclusion cages and simulated abiotic disturbance, I studied the direct and indirect effects of predation by Common Eiders (Somateria mollissima) on an intertidal mussel bed community in Passamaquoddy Bay, New Brunswick, Canada. Eiders fed heavily on blue mussels (Mytilus edulis), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 76 publications
4
56
0
Order By: Relevance
“…This study corroborates a growing body of literature indicating the important effects of sea duck predation on intertidal populations and communities (Guillemette et al 1996, Hamilton 2000, Larsen & Guillemette 2000. The large body size, high metabolic rates, and gregarious nature of sea ducks leads to high rates of predation and potentially important effects on prey abundance.…”
Section: Sea Duck Predation and Community Effectssupporting
confidence: 88%
See 2 more Smart Citations
“…This study corroborates a growing body of literature indicating the important effects of sea duck predation on intertidal populations and communities (Guillemette et al 1996, Hamilton 2000, Larsen & Guillemette 2000. The large body size, high metabolic rates, and gregarious nature of sea ducks leads to high rates of predation and potentially important effects on prey abundance.…”
Section: Sea Duck Predation and Community Effectssupporting
confidence: 88%
“…The presence of sea ducks as a top predator may also affect community dynamics by limiting the abundance of competing predators. Hamilton (2000) found that exclusion of common eiders led to an increase in the abundance of dogwhelks Nucella lapillus, as whelks were likely released from interspecific competition for available mussel prey.…”
Section: Sea Duck Predation and Community Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Sides were left open to avoid accumulation of drifting macroalgae and to minimize potential cage eVects (Hamilton 2000). Non-covered squares were marked at each corner by a stick projecting 5 cm above the sediment surface.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of intertidal area, which was identified as an important predictor of surf scoter distribution in the Malaspina Complex, also was an important environmental factor determining surf scoter distribution in Baynes Sound (Ž ydelis et al, 2006) and has been shown to be important for other sea ducks (including Barrow's goldeneye) in other studies (Esler et al, 2000a, b;Hamilton, 2000). Although habitats in the Malaspina Complex and Baynes Sound are very different (steep rocky shores versus broad intertidal soft-sediment flats, respectively), the intertidal zone is known to be the most important foraging habitat for surf scoters, who dig for clams in soft bottoms and take mussels from hard substrates (Lacroix, 2001;Lewis et al, 2007b).…”
Section: Discussionmentioning
confidence: 85%